CD4 + T Cell Help Confers a Cytotoxic T Cell Effector Program Including Coinhibitory Receptor Downregulation and Increased Tissue Invasiveness - Ahrends, Tomasz; Spanjaard, Aldo; Pilzecker, Bas; Bąbała, Nikolina; Bovens, Astrid; Xiao, Yanling; Jacobs, Heinz; Borst, Jannie (Immunity (Cambridge, Mass.), 2017)
CD4 T cells optimize the cytotoxic T cell (CTL) response in magnitude and quality, by unknown molecular mechanisms. We here present the transcriptomic changes in CTLs resulting from CD4 T cell help after anti-cancer vaccination or virus infection. The gene expression signatures revealed that CD4 T cell help during priming optimized CTLs in expression of cytotoxic effector molecules and many other functions that ensured efficacy of CTLs throughout their life cycle. Key features included downregulation of PD-1 and other coinhibitory receptors that impede CTL activity, and increased motility and migration capacities. "Helped" CTLs acquired chemokine receptors that helped them reach their tumor target tissue and metalloprotease activity that enabled them to invade into tumor tissue. A very large part of the "help" program was instilled in CD8 T cells via CD27 costimulation. The help program thus enhances specific CTL effector functions in response to vaccination or a virus infection.